Membangun Kebiasaan Positif: Pembentukan Karakter untuk Meningkatkan Motivasi Peserta Didik dengan Menerapkan Pembiasaan 'Kembang Sepatu' di SDN Pecabean 01 - Anang; Hanung Sudibyo; Dewi Amaliah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to establish student character formation as a crucial aspect of education. Positive character development is a crucial foundation for future moral, social, and academic development. Positive habit development activities at SDN Pecabean 01 are developed through a habit-building program called 'Kembang Sepatu', an abbreviation of the development activities of SDN Pecabean Satu. The research method used is descriptive qualitative with a case study approach. The research subjects were the principal, teachers, and students in grades I to VI. Data collection techniques included observation, interviews, and documentation of school programs. The results of the study indicate that the implementation of positive habit education at SDN Pecabean 01 is carried out in a programmed manner through routine 'hibiscus' activities including Pacar Cina (a Monday ceremony to increase love for the homeland), Semboja (Tuesday let's learn Javanese), Anyelir (Fun and Enjoyable Literacy on Wednesday), Kamelia (Thursday Produces Innovation and Work), Sabar gen-Z (delicious, tasty and nutritious breakfast together), Jemani (Friday increases faith and cleanliness), and Sepatu (healthy exercise every Saturday).